Strategies of socio-ecological transition for a sustainable urban metabolism - Padovan, Dario; Cristiano, Silvio; Gonella, Francesco (Frontiers in Sustainable Cities, 2022)
Urbanization plays a key role in the human activities causing and feeding climate change. At present, climate change and other environmental issues are directly or indirectly related to the metabolism of cities. However, cities may also play a central role in the fight against climate change. This is the reason why Urban Metabolism (UM) has become a powerful concept to account for and understand the way in which complex systems such as cities use and dispose of material resources, also suggesting measures to change their operational regimes. The rightsizing and optimization of UM is basically a matter of social innovation. It implies changes in the way a city collectively produces and reproduces its physical stocks and provides services to its inhabitants. This article aims at identifying strategies, scenarios, and pathways to slow down urban metabolic processes while improving their efficiency, thus managing a successful transition to an urban (more) circular economy, as well as decreasing the material intensity of the urban economy. The main objectives of the article are the following: 1. The development of a renewed approach for studying Urban Metabolism based on transdisciplinary approaches and methods aimed to model metabolic agents' patterns of practices. 2. The definition of urban patterns of resource use of different agents shaping urban metabolism (households, corporate agents, communities, and public authorities). 3. The exploration of the main policies and administrative tools that cities use to manage environmental problems leading to different urban regulation regimes. 4. A tool for generating future scenarios and roadmaps to reach a low-carbon future. This tool is crucial for engaging experts, stakeholders and the public looking for new solutions.